A small molecule probe reveals declined mitochondrial thioredoxin reductase activity in a Parkinson's disease model. Issue 11 (4th January 2016) - Liu, Yaping; Ma, Huilong; Zhang, Liangwei; Cui, Yajing; Liu, Xiaoting; Fang, Jianguo
Abstract : The first off–on probe, Mito-TRFS, for imaging the mitochondrial thioredoxin reductase (TrxR2) in live cells was reported. Abstract : The first off–on probe, Mito-TRFS, for imaging the mitochondrial thioredoxin reductase (TrxR2) in live cells was reported. In a cellular model of Parkinson's disease (PD), Mito-TRFS staining discloses a drastic decline of the TrxR2 activity, providing a mechanistic link of TrxR2 dysfunction to the etiology of PD.